Calculation the electronic stopping power for charged particles by using Impact parameter - Kadhum, Rashid Aweed; Kadhum, Shahla Abdul sada (Al-Qadisiyah Journal of Pure Science, 2017)
Theoretical study is performed to calculate electronic stopping power by using Bohr equation and the equation which resulting from distant and close collisions which dependent on impact parameter of charged particles ( carbon ions and protons) interacted with organic compounds :[polypropylene (C3H6 ; Ï =0.9 gm/cm3), Polycarbonate (C16H14O3 ; Ï =1.2 gm/cm3), Polyvinylalcohol (C2H4O ; Ï =1.3 gm/cm3), Polyvinylacetate (C4H6O2 ; Ï =1.19 gm/cm3)] by using Bragg rule once and another by the ratio , in the range of energy [ 0.01-1000 ] MeV . This equations are programmed by mathematical methods and done by Matlab language to obtain the required theoretical results and they shown as diagrams .this results compared with program SRIM 2012 to calculate stopping of this compounds ,as they showed a good agreement with them.